2017
DOI: 10.1371/journal.pone.0176982
|View full text |Cite
|
Sign up to set email alerts
|

Indoor residual spraying with micro-encapsulated pirimiphos-methyl (Actellic® 300CS) against malaria vectors in the Lake Victoria basin, Tanzania

Abstract: BackgroundThe indoor residual spraying programme for malaria vectors control was implemented in four districts of the Lake Victoria basin of Tanzania namely Ukerewe, Sengerema, Rorya andSerengeti. Entomological monitoring activities were implemented in one sentinel village in each district to evaluate the efficacy of pirimiphos-methyl 300 CS sprayed on different wall surfaces and its impact against malaria vectors post-IRS intervention.MethodsThe residual decay rate of p-methyl 300 CS applied at a target dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
(52 reference statements)
4
31
0
Order By: Relevance
“…gambiae s.l. from inside to outside biting [25,[27][28][29]. In addition, based on our experience in the eld, the human population spends much more time outside than inside because of the heat as the study area is located in a Sahelian eco-climatic zone of Mali.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae s.l. from inside to outside biting [25,[27][28][29]. In addition, based on our experience in the eld, the human population spends much more time outside than inside because of the heat as the study area is located in a Sahelian eco-climatic zone of Mali.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae s.l. densities between the two areas could be explained by the residual effect of the IRS campaign [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve maximum transfer of PPF particles to high number of mosquitoes visiting the devices optimized PPF formulation will be desirable. For example, particles microencapsulation technology already in use to prolong residual efficacy of chemical insecticides and larvicides [47, 48], could also be used to optimize PPF formulation. On the other hand, the mosquito contamination devices with PPF can be augmented with desirable attractants for different mosquito physiological status to lure relative high numbers of mosquitoes into the device.…”
Section: Discussionmentioning
confidence: 99%
“…The outpatient attendance due to total malaria was 15–18%, a rate lower than the 30–50% national burden [4]. Other studies in Tanzania, Zambia, Zanzibar, Zimbabwe and Benin have showed similar trends in malaria burden after spraying interventions with an organophosphate [14, 23, 26, 34, 35].…”
Section: Discussionmentioning
confidence: 99%